Índices de seleção aplicados aos compostos de milho-pipoca UEM-Co1 e UEM-Co2 sob seleção recorrente - Rocha, Renato da (2014)
The existence of negative correlation between capacity of expansion (CE) and grain yield (GY) has hampered the improvement of popcorn breeding, once the breeder needs to overcome this correlation to achieve his objectives, which consist in obtaining superior genotypes for both traits, CE and GY. However, direct selection may not be satisfactory because it is based on specific attributes of each feature individually. Thus, the selection indexes are the key factor, since they allow the selection of multiple characters, allowing separate superior genotypes, irrespective of the presence or not of correlations between traits. For this, 169 of half-sib families were evaluated in square lattice, 13 x 13, with two replicates for each cycle of selection in the two compounds. The present study had two objectives: the first aim intended to select superior families, through the application of different selection indexes for two compounds of popcorn, UEM-Co1 and UEM-Co2, and in four cycles of recurrent selection. The indexes used were: i) Smith (1936) and Hazel (1943), ii) Williams (1962), iii) Mulamba and Mock (1978), iv) Cunningham et al. (1970), v) Tallis (1962); vi) Pesek and Baker (1969) and vii) Subandi et al. (1973). The second aim was to propose a new and comprehensive selection index of multi-features, the Fi statistics for selection of half-sib families for the same compounds in two cycles of selection (C0 e C1). The use of different selection indexes in 169 half-sib families for compounds UEM-Co1 and UEM-Co2 was efficient, promoting balanced genetic gains for the CE and GY. Subandi et al. (1973) index, followed by Mulamba and Mock (CVg) (1978), were the most effective for both compounds according to Ci statistic. Regarding the appointment of a new selection index, it was found that Fi statistic proved to be efficient in selecting half-sib families, having obtained high gains for CE and GY, higher than the average of selected families by direct selection. Therefore, this index represents a new possibility of selection, in which the breeder has the opportunity to attach greater importance (relative importance - RI) in the characteristics of his interest, being possible, obtain higher gains in more than one x feature, which may overcome the average of those selected by direct selection. The proposed index may be easily applied in other cultures, in which you want to select superior families with genetic gains for multiple features.